If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36x + 16 + 3 = 15 Reorder the terms: 16 + 3 + 36x = 15 Combine like terms: 16 + 3 = 19 19 + 36x = 15 Solving 19 + 36x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 36x = 15 + -19 Combine like terms: 19 + -19 = 0 0 + 36x = 15 + -19 36x = 15 + -19 Combine like terms: 15 + -19 = -4 36x = -4 Divide each side by '36'. x = -0.1111111111 Simplifying x = -0.1111111111
| x^2=63 | | 2r=68 | | -10n+18=-8n-10 | | 355x+2+159x=459-x | | 2x+4=150 | | 7c=56 | | 22-x=3(x+2) | | 75x^10-3x^8=0 | | -X^2-3=0 | | -x+4x-7=3-4x | | X^3-3=0 | | 5-(x+3)=20 | | 6x+2+8=16 | | -7c+6=-22 | | 3x(2x+5)+6x= | | -X^3-3x=0 | | 6(x+8)-2(x-4)=1 | | 4(-4+4x)=-64 | | (5x+6)(3x^2-7x+2)=0 | | 4x+2(x)=8 | | -4(4+2x)=-48 | | x+2(x-1)=3(x-3) | | -4(4v-4)=80 | | 4(1+4n)=68 | | 5x=2.5 | | -3(3+3r)=-45 | | n-13=23 | | 8(2-x)-x=2 | | 3v^2-5v-2= | | 3(3-4x)=45 | | 3(5+c)=2(c+6) | | 7x-(3-x)=3x+4 |